Kernel Sugar Components of Turkish and Foreign Apricot (Prunus armeniaca L.) Varieties - YARILGAC, T.; BOSTAN, S.Z.; KARADENIZ, T.; BALTA, M.F. (Asian Journal of Chemistry, 2010)
This study involves in determining kernel sugar contents of Turkish apricot varieties (Kabaasi, Sakit, Alyanak, Tokaloglu, Salak, Hasanbey, Hacihaliloglu and Sekerpare) and foreign apricot varieties (Paviot, Colomer and Thyrinte) grown in Van (eastern Anatolia, Turkey). The sugar contents of kernels were detected by HPLC. The main sugar was sucrose in the majority of apricot varieties. Kernels of Turkish varieties contained 2.20-5.30 g/100 g sucrose, 0.40-3.40 g/100 g maltose, 0.90-3.64 g/100g glucose and 0.57-5.58 g/100 g fructose. Sugar contents of seeds belonging to foreign varieties were 3.30-4.67 g/100 g sucrose, 1.50-2.52 g/100 g maltose, 3.38-3.72 g/100 g glucose and 1.86-2.93 g/100 g fructose. Sugar contents significantly, differed by varieties. In addition, positive correlation coefficients were computed among kernel sugars.